Clinical profile of patients with pelvic adnexal masses - Sharma, Suksham; Wakhloo, Ajay; Singh, Gagan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Adnexal masses are frequent findings in women of all age groups. It consists of the ovaries, fallopian tubes and uterine ligaments. Women can present with various gynaecological complaints and adnexal masses could be detected while examining and investigating for these complaints. Aim was to study the clinical profile of women in reproductive age group presented with adnexal masses. Methods: The study comprised of 48 women of reproductive age group. Per speculum examination was done and PAP smear was taken before bimanual examination was done.A complete per vaginum examination was done and the adnexal mass was assessed for its size, side, consistency, laterality and tenderness. Results: Pain in the lower abdomen was the commonest chief complaint seen in 87.5% cases. Out of these, majority i.e.66.67% had chronic pelvic pain and 23% had pain of less than 1-month duration which were cases of ectopic pregnancy. 41.67% cases were suspected to have endometriosis,33.33% were suspected to have ovarian cyst, followed by ectopic pregnancy in 16.67% cases and tubo-ovarian mass in 8.33% cases. Conclusions: The present study shows that if proper preoperative evaluation is done, we can select the appropriate patients for laparoscopic approach.